Hand block techniques in traditional and modern sport karate - Sopcic, D.; Janevski, J.; Mudric, R.; Milosavljevic, S. (Sport Science & Practice, 2019)
The paper points to the position and role of block techniques in traditi¬onal and modern sport karate. The realization of blocks in traditional and modern sports karate is essentially different, and those differences represent the focus of this paper. An in-depth analysis underlines those differences not only in terms of execution, but also in terms of training methodology. Understanding the essential differences in the execution of blocks in traditional karate on one side and modern sport karate on the other side can be of crucial importance when it comes to achieving maximum sports results, especially among top athletes. Comprehending the technical differences between blocks, i.e. their implementation in traditional and modern sport karate holds essential importance for the preparation of competitors in modern sport karate, above all for fights. Rejecting the given fact would most certainly have a negative impact in shape of the absence of sports achievements in fights in modern sport karate.